2005
DOI: 10.1073/pnas.0503048102
|View full text |Cite
|
Sign up to set email alerts
|

Foliage shedding in deciduous forests lifts up long-distance seed dispersal by wind

Abstract: Seed terminal velocity and release height are recognized as key biotic determinants of long-distance dispersal (LDD) of seeds by wind. Yet, potential determinants at the ecosystem level, such as seasonal dynamics in foliage density characterizing many deciduous forests, have received much less attention. We integrated detailed field observations and experiments with a mechanistic wind dispersal model to assess how seasonal variation in foliage density, estimated by leaf-area index (LAI), affects LDD in deciduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 36 publications
5
88
0
3
Order By: Relevance
“…2A). The strongest enhancement of wind speed is at the center of wings and corridors because wind in the patches experiences less drag relative to wind at the same height in the surrounding forest matrix due to the lack of tree-canopy obstacles (25). Although the bellowing effect occurs in both winged and connected patches, it only promotes between-patch movement for connected patches ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A). The strongest enhancement of wind speed is at the center of wings and corridors because wind in the patches experiences less drag relative to wind at the same height in the surrounding forest matrix due to the lack of tree-canopy obstacles (25). Although the bellowing effect occurs in both winged and connected patches, it only promotes between-patch movement for connected patches ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, detailed modelling studies of seed flight have shown that turbulence may also increase dispersal distances because structured turbulent eddy motions tend to lift seeds to higher elevations with higher horizontal wind speeds (Horn et al 2001;Nathan et al 2002;Soons et al 2004) There is also an interaction between turbulence and wind speed during seed flight as there is a tendency to higher uplifting by autocorrelated eddies in stronger winds and sparser canopies (Nathan et al 2002;Soons et al 2004;Nathan & Katul 2005), and by thermal updrafts that tend to develop only in relatively weak winds (Tackenberg 2003). However, the effect of turbulence on the seed abscission phase was not included in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The LDD of wind-dispersed seeds and pollen is typically promoted by turbulent vertical fluctuations in wind and by coherency in vertical eddy motion that uplifts seeds well above the vegetation canopy (Nathan et al 2002;Tackenberg 2003;Soons et al 2004;Nathan & Katul 2005;. Turbulent wind conditions can be induced by atmospheric instability that, among other factors, depends on temperature differences between the surface and the atmosphere (Monin & Obukhov 1954), which generates the socalled convective (thermal) turbulence (e.g.…”
Section: Introductionmentioning
confidence: 99%